2017
DOI: 10.1074/jbc.m116.747006
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid down-regulates expression of the selenoprotein P gene by inhibiting SREBP-1c protein independently of the AMP-activated protein kinase pathway in H4IIEC3 hepatocytes

Abstract: Selenoprotein P (encoded by in humans, in rat), a liver-derived secretory protein, induces resistance to insulin and vascular endothelial growth factor (VEGF) in type 2 diabetes. Suppression of selenoprotein P may provide a novel therapeutic approach to treating type 2 diabetes; however, few drugs inhibiting expression in hepatocytes have been identified. The present findings demonstrate that eicosapentaenoic acid (EPA) suppresses expression by inactivating sterol regulatory element-binding protein-1c (SREBP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 55 publications
2
33
0
1
Order By: Relevance
“…There are also reports on the suppressing effect of metformin on selenoprotein P production in the liver, which contributes to the improvement of IR, however this was not investigated on human samples [ 56 , 57 ]. Tajima-Shirasaki N. et al presented that eicosapentaenoic acid (EPA), a component of ω-3 PUFAs (polyunsaturated fatty acids), inhibits SeP expression in rat hepatocytes [ 58 ]. Although, the data concern an animal model, they correlate with the wide literature data proving EPA deficiency in subjects with psoriasis and the beneficial effect of ω-3 PUFA supplementation on their clinical improvement [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports on the suppressing effect of metformin on selenoprotein P production in the liver, which contributes to the improvement of IR, however this was not investigated on human samples [ 56 , 57 ]. Tajima-Shirasaki N. et al presented that eicosapentaenoic acid (EPA), a component of ω-3 PUFAs (polyunsaturated fatty acids), inhibits SeP expression in rat hepatocytes [ 58 ]. Although, the data concern an animal model, they correlate with the wide literature data proving EPA deficiency in subjects with psoriasis and the beneficial effect of ω-3 PUFA supplementation on their clinical improvement [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that PUFAs not only maintain energy production throughout the body but also regulate the biological processes in cells. The recently published article demonstrated that eicosapentaenoic acid (EPA, 20:5n‐3) suppressed SELENOP gene expression by inactivating its transcriptional regulation (Tajima‐Shirasaki et al, ). In mammal, it has been identified that α‐linolenic acid (ALA, 18:3n‐3) is initially converted to stearidonic acid (SDA, 18: 4n‐3) by the Δ6‐desaturase (FADS2), and further is elongated and desaturated into EPA (Burdge & Calder, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, eicosapentaenoic acid (EPA), a major component of w-3 polyunsaturated fatty acids (PUFAs) contained in fish oil, has been reported to decrease SeP expression in H4IIEC3 hepatocytes. (64)(65)(66) EPA is used to improve lipid metabolism and has beneficial effects in the treatment of type 2 diabetes. EPA has been known to activate AMPK; however, EPA decreases the binding of sterol regulatory element-binding protein-1c (SREBP-1c) to the SeP promoter region and lowers SeP levels.…”
Section: Increase Of Sep Levels Under High Glucose and High Fat Condimentioning
confidence: 99%
“…Metformin and EPA decrease SeP mRNA expression. (61,64) However, these diabetes drugs are not effective against PAH-PASMC proliferation, which suggests other molecular mechanisms that increase SeP expression in PAH. (77) To inhibit the SeP expression in PAH-PASMCs, sanguinarine, a plant alkaloid, has been identified by highthroughput screening of 3,336 compounds.…”
Section: Therapeutic Strategies To Treat Increased Sepmentioning
confidence: 99%